2002
DOI: 10.1186/1471-2253-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Acute Normovolaemic Hemodilution (ANH) in combination with Hypotensive Epidural Anaesthesia (HEA) during knee arthroplasty surgery. No effect on transfusion rate. A randomized controlled trial [ISRCTN87597684]

Abstract: Background: Hypotensive epidural anaesthesia (HEA) combines a high epidural anaesthesia, performing a sympathetic blockade, with low-dose iv-infusion of epinephrine to stabilize circulation in the conscious patient. Mean artery blood pressure is reduced to 45-50 mmHg and hereby a reduced blood loss. In this study we have combined HEA with preoperative acute normovolaemic hemodilution (ANH) in attempt to further reduce the blood loss and need for blood transfusion in total knee arthroplasty surgery (TKR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Indeed, bleeding during and after TKA is often associated with cardiovascular complications and a high transfusion rate of allogenic blood [4]. Recently, drainage clamping, associated with epinephrine solution infusion, has been shown to be effective at reducing blood loss.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, bleeding during and after TKA is often associated with cardiovascular complications and a high transfusion rate of allogenic blood [4]. Recently, drainage clamping, associated with epinephrine solution infusion, has been shown to be effective at reducing blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Since allogenic blood transfusion increases the risk of immunological and non-immunological adverse effects for the patients and increases medical costs [2,4], intraoperative use of norepinephrine should be considered as an effective method of preventing these severe complications and reducing the cost of blood management in knee replacement surgery. This is the first study in which the reduction of blood loss and allogenic blood transfusion requirements in TKA have been achieved by the simple expedient of local administration of norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,21,30,40,47,62,65 These studies revealed that the overall volume of perioperative blood loss was similar in the PANH group and the control group (WMD, 21.98 mL; 95% CI, −46.90 to 90.86 mL; P = 0.53). These results are presented in the forest plot in Figure 4.…”
Section: Volume Of Perioperative Blood Lossmentioning
confidence: 72%